WIWITAN EQUIPMENT AS BATIK MOTIF CREATION FOR MODERN KEBAYA - listya iswandari, aviva; -, Guntur (Indonesian Institute of the Arts Surakarta, 2024)
The main ideas that became the basis for the batik motif on jarik for modern kebaya clothing was offering equipment in wiwitan tradition. The wiwitan tradition in traditional agricultural practice is a ceremony carried out by the community before harvesting, wiwitan is a tradition that deserves to be maintained and preserved and can even be developed in its ritual procession to become its own attraction. Basically, this tradition is an expression of gratitude to God. The rituals of this tradition completed with offerings and bancakan which are a form of gratitude for all the favors and blessings of God to the earth. The content of the offerings or known as uborampe was used as a source of inspiration for the creation of batik motifs on jarik for modern kebaya. The creation of batik motif is carried out by means of batik tulis that is styled contemporary then colored with remasol dye and colet technique. The colors used are brown, cream, brick red, purple, grey, blue, and pink. Batik with wiwitan offering motifs is equipped with modern kebaya to create total of 4 designs completed with sequins as decoration and veil as a head-wear to make it look elegant and appropriate for both formal and non-formal events.